Temoporfin-Conjugated Upconversion Nanoparticles for NIR-Induced Photodynamic Therapy: Studies with Pancreatic Adenocarcinoma Cells In Vitro and In Vivo - Oleksandr Shapoval; David Větvička; Vitalii Patsula; Hana Engstová; Olga Kočková; Magdalena Konefał; Martina Kabešová; Daniel Horák (MDPI AG, 2023)
Upconverting nanoparticles are interesting materials that have the potential for use in many applications ranging from solar energy harvesting to biosensing, light-triggered drug delivery, and photodynamic therapy (PDT). One of the main requirements for the particles is their surface modification, in our case using poly(methyl vinyl ether-alt-maleic acid) (PMVEMA) and temoporfin (THPC) photosensitizer to ensure the colloidal and chemical stability of the particles in aqueous media and the formation of singlet oxygen after NIR irradiation, respectively. Codoping of Fe2+, Yb3+, and Er3+ ions in the NaYF4 host induced upconversion emission of particles in the red region, which is dominant for achieving direct excitation of THPC. Novel monodisperse PMVEMA-coated upconversion NaYF4:Yb3+,Er3+,Fe2+ nanoparticles (UCNPs) with chemically bonded THPC were found to efficiently transfer energy and generate singlet oxygen. The cytotoxicity of the UCNPs was determined in the human pancreatic adenocarcinoma cell lines Capan-2, PANC-01, and PA-TU-8902. In vitro data demonstrated enhanced uptake of UCNP@PMVEMA-THPC particles by rat INS-1E insulinoma cells, followed by significant cell destruction after excitation with a 980 nm laser. Intratumoral administration of these nanoconjugates into a mouse model of human pancreatic adenocarcinoma caused extensive necrosis at the tumor site, followed by tumor suppression after NIR-induced PDT. In vitro and in vivo results thus suggest that this nanoconjugate is a promising candidate for NIR-induced PDT of cancer.